Kepemimpinan dan Konsultasi: Pola Komunikasi Kepala Desa dengan Badan Permusyawaratan Desa di Indonesia - Yogi, Yogi; Tuanaya, Wahab; Latuconsina, Nurrainy (Universitas Pattimura, 2024)
This study aims to analyze the communication patterns between Village Heads and the Village Consultative Council (BPD) in village governance in Indonesia, focusing on aspects of leadership and consultation. Effective communication between these two actors is key to realizing participatory and responsive village governance that aligns with community aspirations. The study employs a qualitative approach using a case study method in Gale-Gale Village, Seram Bagian Barat Regency. Data collection was conducted through in-depth interviews, participatory observation, and document analysis. The findings reveal that although communication between Village Heads and the BPD has been established through cooperation, consultation, and coordination, its utilization in implementing core governance functions remains suboptimal. The main obstacle identified is the lack of understanding among BPD members regarding their roles as stipulated in existing regulations, which affects the coordination process in conveying community aspirations. Additionally, limited infrastructure impacts the effectiveness of communication at the village governance level. The novelty of this study lies in identifying the gap between regulation and communication practices in village governance, highlighting the need to enhance the capacity of BPD members to perform their functions more effectively. This study recommends strengthening training and socialization programs for BPD members and developing a more systematic communication mechanism to improve synergy between Village Heads and the BPD in fostering more democratic and inclusive village governance. These findings contribute to the development of social sciences and humanities, particularly in the study of local leadership and political communication at the village level.